Rigid Fiber-Optic Device Intubation in a Child With Temporomandibular Joint Ankylosis. Issue 2 (March 2020) - Vitkovic, Bibiana; Milic, Morena; Filipan, Dorotea; Dediol, Emil
Abstract : Abstract: The authors present a case of rigid fiber-optic device intubation in an 8-year-old boy with posttraumatic temporomandibular joint ankylosis. For this intention, a 5 mm diameter Bonfils fiberscope was used. Such practice has never been described before in pediatric patients with temporomandibular joint ankylosis. The procedure was successful and without complications. Therefore, the authors conclude that this method represents a useful alternative in difficult airway management in children with limited mouth opening.